TEENAGERS AND MOTIVATION: A STUDY ON THE REASONS FOR NOT PRACTICING PHYSICAL AND SPORTS ACTIVITY. (Fiep Bulletin - online, 2011)
The practice of physical and sports activities has been considered as one of the relevant components within a healthy lifestyle, since its practice in a regular systematic way and with certain intensity constitutes a factor which promotes health. The present study attempts to establish what are the reasons why 15, 16 and 17 year old teenagers don't practice physical and sports activity. This investigation is characterized as quantitative, of non-experimental methodology, has as a study type, the Transversal one and a questionnaire as an instrument. As results, it was found that teenagers considered, as reasons for not practicing physical and sports activity as a habit, lack of time, lack of motivation, the fact that there's no place to practice it, and health issues.
Keywords: Teenagers; Motivation; Physical Activity